Feasibility study of an underground reservoir with an integrated pumped-storage hydropower system (discharge consideration) - Huang, Shijie (2017)
Singapore has been plagued by water supply issues since its independence in 1965. With limited land to collect and store rainwater, Singapore has to innovate and strategise to actively develop capabilities and secure a sustainable supply of water for the nation. Furthermore, Singapore is not completely insulated from the influences of climate change. A rise in the intensity of weather variability could present significant challenges to Singapore’s water resources management. Therefore, Singapore’s national water agency, Public Utilities Board (PUB), is exploring the feasibility of constructing an underground drainage and water reservoir system which could mitigate the impact of climate change and to provide an auxiliary storage against droughts. A pumped-storage hydropower system can also be integrated in the system to harvest the energy of the stormwater in the tunnels as it makes the drop into the underground reservoir.